Islamic Political Economy: Critical Review of Economic Policy in Indonesia - Ropi Marlina; J. Juliana Juliana; N. Amalia Adila; M. Bilal Robbani (Review of Islamic Economics and Finance (RIEF), 2019)
This article is based on a phenomenon of inequality that occurs in Indonesia, which is still quite high. Besides, the current reality shows that the implementation of political economy has not been able to meet the primary needs of each individual. This article aims to describe and elaborate on the concepts and objectives of the Islamic political economy. The qualitative descriptive method is used with a literature review approach with sources from books, journals, news, and other sources relevant to the title. The results of the discussion of this article show that economic politics in the perspective of Islam has a different perspective from capitalists. Islamic Political Economics aims to fulfill each individual's primary needs (food, shelter, and clothing). In implementing the Islamic Political Economy, the state has an important role, either directly or indirectly. As for case studies in Indonesia, regarding aspects of fulfilling food needs, it is ranked 73rd globally with a GHI of 21.9. This is a huge number at a serious level. The number shows that the Indonesian government has not been able to fulfill one of the political goals of Islamic economics, namely the fulfillment of each individual's food. In addition, in terms of security, education and health have not also been well fulfilled. It is expected that this writing will become a reference and add to the treasure of thought regarding the Islamic economy.